(De)constructing the sociological imagination? Media discourse, intellectuals and the challenge of public engagement. (October 2016) - Attenborough, Frederick T
This article explores the interrelationships and tensions between public engagement in higher education and media discourse. It tracks the mediated trajectory of an attempt by a group of academics to connect with audiences beyond academia, comparing a magazine article in which their opinions first became public, to its recontextualisation across various UK newspapers and their Internet spin-offs. A mediated stylistic analysis reveals the discursive, rhetorical and performative techniques via which a sociologically imaginative attempt to transform a seemingly-personal-trouble into a definitively-public-issue got recontextualised as if merely the public projection of personal angst. The article concludes by noting that in an era where public engagement increasingly means mediated public engagement, to take seriously the interactive, intertextual and rhetorical affordances of media discourse is to understand that and how sociologically imaginative work can – but does not always – end up circulating within public debate.